Exploring the construct of anticipatory stress in finding a job after residency training through cognitive interviewing: Implications for learner well-being and health workforce planning [version 1; peer review: 1 approved, 2 approved with reservations] - Megan Thomas; Aliya Kassam; Kent Hecker; Sana Jawad (MedEdPublish, 2023)
Background: Anticipatory stress (AS) is denoted by concern about future events for which there is little control. Most AS research has been physiological studies such as measuring salivary cortisol levels.   Medical learners may experience AS regarding employment after residency, however anticipatory stress AS a psychological construct across career stages has not previously been studied. The objective of this study is to explore the psychological construct of employment AS in medical students, residents, and former Program Directors (PDs).   Methods: Participants were recruited from a large Canadian medical school via purposive sampling. Semi-structured interviews with n=21 participants (six medical students, nine residents, and six PDs) were transcribed verbatim, and coded by two independent reviewers using thematic analysis.   Results: Participants agreed that financial, family, and geographical factors exacerbate AS, and it is mitigated by flexibility, social support, and being proactive. External support, job market saturation, and differences between medical specialties also influence AS. Perspectives unique to participant groups included: medical students reflecting on a hidden curriculum and preoccupation with proximal issues over distal concerns of employment; residents experiencing competing residency program demands; former PDs finding that resident competency, yearly hiring fluctuations, and existing stress impact AS. Consequences of AS include physical and psychological manifestations, performance anxiety, and pursuing additional training.   Conclusions: Perceptions of AS vary by medical career stage. Individual, program and systems-level changes can help manage and address the underlying cause of AS: an unreliable job market for physicians. Correcting the mismatch between residency positions and job openings may be a proactive, preventative approach.